The cultivation of house plants - Ritner, Jennie Inez (My University, 1906)
Introduction: So many people condemn the cultivation of house plants, saying that it is just a waste of time because you get nothing for all your work and you might spend your time a great deal more profitably in growing something to eat or to sell. These people evidently see only the money side of life. They do not take into consideration that there are other valuable things to be gained in this world besides money and while their value cannot be measured according to a fixed money standard, still they are just as essential to a person’s existence and perhaps more so. One of the first and important qualities which the cultivation of house plants contribute to an individual is their refining influence. People who cultivate flower plants see the beauty in them and from these they are taught to see the other beautiful things which surround them. Another quality which the house plants contribute is pleasure. All persons who love plants experience a genuine thrill of pleasure as they watch the growth of some choice plant, seeing the little leaves develop and gradually reach maturity, or it may be some bud which has been watched over tenderly and is now unfolding its little petals revealing the wonderful beauty that nature and man’s care are able to give.
Citation: Ritner, Jennie Inez. The cultivation of house plants. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Botany; Plant Propagation; House Plants; Plant Pests; Theses; Manuscripts (documents)